Investment attractiveness of Ukraine: realities and perspectives - Victoria Zalizniuk; Volodymyr Shchelkunov (Економічний вісник університету, 2021)
Subject of research. The purpose of the study is the investment attractiveness of Ukraine and ways to improve using the Index of Investment Attractiveness of Ukraine. The purpose of writing this article is to identify ways to improve the investment climate in Ukraine. Methodology of work - methods of statistical analysis and synthesis, method of graphic modeling of investment attractiveness of economic climate in Ukraine. Results - As a result of the study, the following priorities were identified for 2021 to improve the investment climate in Ukraine: a reboot of the judicial system; de-oligarchization of power; development of an effective and independent anti-corruption infrastructure; getting rid of bureaucracy; reduction of administrative and tax pressure on business; appointment of pro-European reformers to public office; restoration and support of cooperation with international financial institutions; law enforcement reform and effective fight against smuggling, including through increased fiscalization; establishing equal rules of the game for business. Scope of results. Economic branch: management of the national economy, macroeconomics, economic theory. Conclusions. The biggest obstacles to the Ukrainian market as a result of the survey identified - exchange rate fluctuations, close ties between the economy and politics, insufficient legal order, corruption of public authorities, labor shortages and access to finance.